Eco-translatology: A study on the English Translation of Gayo’s Narrative "The Legend of the Origin of Depik" - Susidamaiyanti; Meisuri; Dirgeyasa, I Wy.; Ramadhani, Kartina; Sianipar, Rafita Tioria (JL3T (Journal of Linguistics, Literature and Language Teaching), 2023)
Eco-translatology, an emerging field focusing on ecological-themed texts and sustainable translation practices, was explored in the translation of the Gayo narrative--“The Legend of the Origin of Depik”-- The study investigated the strategies employed in the translation process through qualitative content analysis. Interpretation is examined from linguistic, cultural, and communicative dimensions using Hu's (2001) three-dimensional adaptation and selection theory. The findings showed that strategies like “emptying,” “compensating,” and “leaning on” were used, however, the translation faced challenges in attaining accuracy, cultural connotations, and effective communication. Translators must prioritize these aspects to achieve a faithful rendition, aligning eco-translatology’s three-dimensional adaptation and selection theory. This research emphasizes the importance of environmental awareness in translation and highlights the need for further attention to ensure successful ecological and culturally sensitive translations.